If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + -2s = 7 + -2k Solving 6k + -2s = 7 + -2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2k' to each side of the equation. 6k + 2k + -2s = 7 + -2k + 2k Combine like terms: 6k + 2k = 8k 8k + -2s = 7 + -2k + 2k Combine like terms: -2k + 2k = 0 8k + -2s = 7 + 0 8k + -2s = 7 Add '2s' to each side of the equation. 8k + -2s + 2s = 7 + 2s Combine like terms: -2s + 2s = 0 8k + 0 = 7 + 2s 8k = 7 + 2s Divide each side by '8'. k = 0.875 + 0.25s Simplifying k = 0.875 + 0.25s
| x^2+10x+25-y^2=0 | | 3(d-8)-5=9(d+2)-1 | | A*4-60=A | | 3(5x-4)=8x+12 | | 7+21m=42+14m | | 69+25= | | 69=x-(-5) | | 3.1+7.3= | | 15x+3.5=2 | | 14x+3=7x+9 | | 117=n+40 | | -54=m+(91) | | 8+15p-1=8p+98-6p | | 2y-15+3y=60 | | -89=-80-x | | X^2+36+180=0 | | 15x-5=50 | | -11+x=-11 | | -9x-1.4=5.8 | | 2x+2=89 | | 2(a-5)=2(q+5) | | -12-n=-10 | | (9y^2-6y+9)-(5y^2-6y+8)= | | 3(a-8)+7=5(a+2)-3a-19 | | 8x-6=130 | | -17-v=-5 | | -4x+8+12=44-48 | | 2(6-4d)=2s-9d | | 5=x-(-28) | | 2x-x-10=-13 | | -74=6+10x | | 14x+4=116 |